Pengembangan Lembar Kerja Peserta Didik Berbasis Keterampilan Proses Sains Pada Materi Sistem Peredaran Darah Kelas XI SMA/MA - Rahayu, Syamsiar; Nurhayati B, Nurhayati B; Idris, Irma Suryani (Biology Teaching and Learning, 2021)
Abstract. This study aims to produce a student worksheet based on science process skills on bloodsirculation system for XI grade. The type of this research is Research & Development (R & D). Thedevelopment of this worksheet used ADDIE models. The stages of ADDIE are Analyze, Design, Develop,Implement and Evaluate. Research instrument validated by two experts. Validation score is 4.17 or on range highly valid. Teacher‟s mean score is 96,87 in the other meaning is easily to be used, while the student‟smean score is 73,33 or easily practiced (both number interpreted based on the range score used). Based onthe results, it can be concluded that the development of electronic student worksheet based on scienceprocess skills on blood circulation system for XI grade is valid and practical.Keywords: worksheet, science process skills, valid, practical.